Enhancing Students’ Reading Comprehension of Recount Texts through Comic Strips: A Classroom Action Research at SMP Negeri 4 Padangsidimpuan - Fahmi, Muhammad; Maharani; Harahap, Tinur Rahmawati (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
This classroom action research aims to investigate the effectiveness of comic strips in enhancing students' reading comprehension of recount texts. The study was conducted at SMP Negeri 4 Padangsidimpuan during the 2023–2024 academic year, involving 60 eighth-grade students. The research design followed two cycles of Classroom Action Research (CAR), each consisting of planning, acting, observing, and reflecting stages. Data were collected through a pre-test, post-test 1, and post-test 2, supported by classroom observation. The results revealed a significant improvement in students’ reading performance. The mean score increased from 53.67 in the pre-test to 68.08 in post-test 1, and finally to 81.92 in post-test 2. The percentage of students who passed the minimum competency standard (KKM) rose from 3.33% to 86.67%. These findings demonstrate that comic strips are an effective instructional medium that can foster student motivation, support vocabulary development, and improve comprehension of text structures in recount writing. This study concludes that the use of comic strips can significantly enhance reading comprehension skills and should be considered as an engaging and pedagogically valuable tool in English language classrooms.